Pengaruh Kinerja Lingkungan dan Women On Board terhadap Nilai Perusahaan dengan Komisaris Independen sebagai Variabel Moderasi - Dandy Bintang Taufik Ridho; Christina Dwi Astuti (Journal of Management and Bussines (JOMB), 2024)
This research aims to empirically test the influence of environmental performance and the presence of women on board on company value, with an independent board of commissioners as a moderating variable. This type of research is quantitative causality with the use of secondary data. The population of this research is industrial sector companies listed on the Indonesia Stock Exchange (BEI) during the period 2020 to 2022. The research sample was 89 companies selected using a purposive sampling method. Data analysis was carried out using panel data regression analysis using Eviews 9.0 statistical software. The research results show that environmental performance and the presence of women on board do not have a significant influence on company value. However, an independent board of commissioners has been proven to be able to strengthen the influence of environmental performance and women on board on company value. The conclusion is that the existence of an independent board of commissioners plays an important role in optimizing the positive impact of environmental performance and the presence of women on board on company value. Keywords: Company Values, Environmental Performance, Women on Board, Independent Board of Commissioners